Synthesis, structure, and mechanical properties of silica nanocomposite polyrotaxane gels - Kato, Kazuaki; Matsui, Daisuke; Mayumi, Koichi; Ito, Kohzo (Beilstein Journal of Organic Chemistry, 2015)
A significantly soft and tough nanocomposite gel was realized by a novel network formed using cyclodextrin-based polyrotaxanes. Covalent bond formation between the cyclic components of polyrotaxanes and the surface of silica nanoparticles (15 nm diameter) resulted in an infinite network structure without direct bonds between the main chain polymer and the silica. Small-angle X-ray scattering revealed that the homogeneous distribution of silica nanoparticles in solution was maintained in the gel state. Such homogeneous nanocomposite gels were obtained with at least 30 wt % silica content, and the Young’s modulus increased with silica content. Gelation did not occur without silica. This suggests that the silica nanoparticles behave as cross-linkers. Viscoelastic measurements of the nanocomposite gels showed no stress relaxation regardless of the silica content for <20% compression strain, indicating an infinite stable network without physical cross-links that have finite lifetime. On the other hand, the infinite network exhibited an abnormally low Young’s modulus, ~1 kPa, which is not explainable by traditional rubber theory. In addition, the composite gels were tough enough to completely maintain the network structure under 80% compression strain. These toughness and softness properties are attributable to both the characteristic sliding of polymer chains through the immobilized cyclodextrins on the silica nanoparticle and the entropic contribution of the cyclic components to the elasticity of the gels.
Keywords: cyclodextrin; gel; mechanical property; nanocomposite; polyrotaxane

(untitled) - Mitsumata, T.; Ohori, S. (Polym. Chem., 2011)

(untitled) - Fujiwara, S.; Fujimoto, K. (Rubber Chem. Technol., 1971)

(untitled) - Kaufman, S.; Slichter, W. P.; Davis, D. O. (J. Polym. Sci., Part A-2: Polym. Phys., 1971)

(untitled) - Nishi, T. (J. Polym. Sci., Polym. Phys. Ed., 1974)

(untitled) - O’Brien, J.; Cashell, E.; Wardell, G. E.; McBrierty, V. (Macromolecules, 1976)

(untitled) - Nishi, T.; Nukaga, H.; Fujinami, S.; Nakajima, K. (Chin. J. Polym. Sci., 2007)

(untitled) - Brochu, P.; Pei, Q. (Macromol. Rapid Commun., 2010)

(untitled) - Wenz, G.; Han, B.-H.; Müller, A. (Chem. Rev., 2006)

(untitled) - Harada, A.; Hashidzume, A.; Yamaguchi, H.; Takashima, Y. (Chem. Rev., 2009)

(untitled) - Okumura, Y.; Ito, K. (Adv. Mater., 2001)

(untitled) - Murata, N.; Konda, A.; Urayama, K.; Takigawa, T.; Kidowaki, M.; Ito, K. (Macromolecules, 2009)

(untitled) - Kato, K.; Ito, K. (Soft Matter, 2011)

(untitled) - Bitoh, Y.; Akuzawa, N.; Urayama, K.; Takigawa, T.; Kidowaki, M.; Ito, K. (Macromolecules, 2011)

(untitled) - Mayumi, K.; Tezuka, M.; Bando, A.; Ito, K. (Soft Matter, 2012)

(untitled) - Katsuno, C.; Konda, A.; Urayama, K.; Takigawa, T.; Kidowaki, M.; Ito, K. (Adv. Mater., 2013)

(untitled) - Kato, K.; Yasuda, T.; Ito, K. (Polymer, 2014)

(untitled) - Seo, J.-H.; Kakinoki, S.; Inoue, Y.; Yamaoka, T.; Ishihara, K.; Yui, N. (J. Am. Chem. Soc., 2013)

(untitled) - Ito, K. (Polym. J., 2012)